1999
DOI: 10.1002/ctpp.2150390504
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of a Chemically Active, Pulsed Microwave Plasma for Deposition of Quartz‐like Films

Abstract: A remote microwave plasma has been used for the deposition of scratch-resistant quartz-like films. Process gases are argon, oxygen, and hexamethyl-disiloxane. Input power is modulated and the effects on the plasma as well as on the deposition process are studied by means of various diagnostic methods. The film deposition rate is slightly reduced under most conditions but film quality (i.e., cluster size, roughness, scratch resistance) may be improved. A precursor has been identified by mass spectrometric measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[ 90 ] At higher pressure (40−70 Pa) and lower T e (clearly below 2 eV), on the contrary, no deposition rate could be observed in an HMDSO remote plasma of an MW plasma source. [ 91,92 ] Activation reactions with oxygen were required to initiate film growth when ion bombardment was negligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 90 ] At higher pressure (40−70 Pa) and lower T e (clearly below 2 eV), on the contrary, no deposition rate could be observed in an HMDSO remote plasma of an MW plasma source. [ 91,92 ] Activation reactions with oxygen were required to initiate film growth when ion bombardment was negligible.…”
Section: Resultsmentioning
confidence: 99%
“…[ 100 ] Likewise, no deposition was achieved with Ar/HMDSO in a microwave remote plasma at 40−70 Pa, primarily yielding CH 3 abstraction from HMDSO at low T e . [ 91,92 ] It should be noted that the observed energy threshold for the lumped activation reaction of 14 ± 1 eV lies in between the (average energy loss‐weighted) Ar excitation and ionization energies with 12.14 and 15.76 eV, respectively. The observed exponential increase in k a for T e < ~2 eV, thus, appears to be consistent.…”
Section: Resultsmentioning
confidence: 99%
“…Parallel to the experiment described in this paper, we performed a deposition experiment using hexamethyldisiloxane (HMDSO) in pulsed oxygen plasmas generated by the same type of plasma source. As reported in [2], film properties like homogeneity and roughness can be controlled by a variation of pulse frequency. In some qualitative considerations on the deposition process, it is suggested that atomic oxygen plays a role in two ways: on the one hand, it is used for the formation of precursors; on the other hand, it oxidizes hydrocarbon compounds which otherwise would be integrated into the growing film.…”
Section: Introductionmentioning
confidence: 92%
“…a 23 stands for the branching ratio of the fluorescence transition. σ (2) is the cross section of the two-photon transition, whereas g( ω)…”
Section: Absolute Calibration By Two-photon Transition Of Xenonmentioning
confidence: 99%
See 1 more Smart Citation